Assessment of levofloxacin effect on human neutrophil functions in vitro [Levofloksasin'in insan Nötrofil fonksiyonlari üzerine etkisinin in vitro deǧerlendirilmesi] - (:unkn) unknown (My University, 2013)
The aim of the study was to determine the effects of levofloxacin on the phagocytic and intracellular killing functions of human neutrophils at different therapeutic concentrations and to investigate the possible differences between pure powder and pharmaceutical form of levofloxacin on the neutrophil functions. Neutrophils obtained from healthy volunteers were incubated with both pure powder and pharmaceutical form of levofloxacin at different concentrations (1.4 μ/mL, 2.8 μ/mL, 5.7 μ/mL, 11.4 μ/mL). At concentrations of 2.8 μ/mL solutions, prepared from both pure powder and pharmaceutical form of levofloxacin, were observed to decrease phagocytosis and intracellular killing comparing to control samples, but only the decrease for the pharmaceutical form's effect on phagocytic function was statistically significant (p<0.05). At concentration of 2.8 μ/mL solution, prepared from pharmaceutical form of levofloxacin, was observed to statistically significant decrease phagocytosis comparing to 2.8 μ/mL solution prepared from pure powder of levofloxacin (p<0.05). At concentration of 5.7 μmL solution, prepared from pharmaceutical form of levofloxacin, was observed to statistically significant decrease phagocytosis and intracellular killing comparing to 5.7 μ/mL solution prepared from pure powder of levofloxacin (p<0.05). Phagocytic activity of neutrophils was significantly decreased by levofloxacin solution prepared from pure powder at concentrations of 11.4 μ/mL when compared with control (p<0.05). As conclusion, the solutions prepared with pharmaceutical form have significantly inhibition on the phagocytic and intracellular killing functions of human neutrophils in vitro when comparing with the solutions prepared with pure powder.
Keywords: Intracellular killing; Levofloxacin; Neutrophil; Phagocytosis